China and the Middle East: venturing into the maelstrom - Dorsey, James M. (2016)
China’s increasingly significant economic and security interests in the Middle East have several impacts. It affects not only its energy security but also its regional posture, relations with regional powers as well as the United States, and efforts to pacify nationalist and Islamist Uighurs in its north-western province of Xinjiang. Those interests are considerably enhanced by China’s One Belt, One Road initiative that seeks to patch together a Eurasian land mass through inter-linked infrastructure, investment and expanded trade relations. Protecting its mushrooming interests is forcing China to realign its policies and relationships in the region.